Credit Constraints, Technology Choice and Exports: A Firm‐level Study for Latin American Countries. Issue 2 (May 2016) - Hasan, Syed; Sheldon, Ian
Abstract: In this paper, constraints on technology choice and credit access are introduced into a firm‐level trade model in a dynamic setting in order to explain factors that limit benefits to a firm from trade liberalization. Theoretical analysis shows that firms face credit constraints depending on their initial productivity and the cost of credit. As a result, credit‐constrained firms may not be able to cross the minimum productivity threshold needed to enter and compete in a foreign market. Empirical analysis using firm‐level panel data for six Latin American countries confirms that financial constraints negatively influence firms' export and investment decisions.